Pentingnya Pengembangan Kurikulum Berorientasi Revolusi Industri 4.0 - Muhammad Irwan Padli Nasution; Nurbaiti Nurbaiti (Query: Journal of Information Systems, 2020)
The dynamic ability of human thinking always brings changes in science and technology from time to time. The development of science and technology has changed the world into what it is today, and will continue in the future. The fourth generation, industrial revolution shows the latest trends in automation and data exchange in technology, including cyber-physical systems, internet for everything, cloud computing, and cognitive computing. Along with the industrial revolution 4.0 and digital technology, business competition and development that originally relied on the use of natural resources will shift to mastery of information technology and workforce competence. Human Resource Competence is an important point to encourage a country to evolve to the next generation of industry, and Indonesia is no exception. The important role of universities to provide workers who have the skills and competencies required by a quality market will also be able to produce leaders and thinkers of a nation who will determine the development of their country in the future. Universities are given by the state to manage study programs that specialize in their fields of science. The study program plays a role in compiling or adjusting the curriculum, facilitating students who will take learning and other academic activities, it is very necessary to adjust the curriculum according to market needKeywords:  Curriculum, Competencies, Industrial revolution, Indonesia, University